Psychological Literacy and Undergraduate Psychology Education: An International Provocation - Cranney, Jacquelyn; Dunn, Dana S.; Hulme, Julie A.; Nolan, Susan A.; Morris, Sue; Norris, Kimberley (Frontiers in Education, 2022)
For over fifty years, psychology leaders have called for fundamental changes in how we undertake research, education, and community interaction. This paper provocatively argues the case for ‘why now, and how’. The COVID-19 pandemic has demonstrated that psychology must contribute more fully to the wellbeing and prosperity of local and global communities. We propose that a primary mechanism for doing so is by reinventing the undergraduate psychology program. This paper provides a stimulus to initiate international discussion of (with its numerous graduates), to emphasize nine interconnected graduate capabilities, which we propose to be: Knowledge, Methods, Application to Personal, Professional and Community (Local, National, Global) Domains, Ethics & Values, Critical Thinking, Communication, and Cultural Responsiveness. Focusing on core aspects of psychology (Knowledge, Research Methods, Application) and more generic but evidence-based informed capabilities is a unique formulation and should well serve graduates, employers, society, and the psychology discipline and profession in the uncertain ‘post-pandemic’ era. We also propose psychological literacy as a promising unifying approach for psychology. Finally, we uniquely provide a ‘road-map’ for curriculum renewal at international, national, and institutional levels, involving a consensus-seeking process for internationally agreed graduate capabilities (an extensive scholarly overview of the proposed capabilities is provided in Supplementary Materials), and the concurrent location and development of teaching and assessment resources accessible to all nations.